EFFECT OF OPENIINGS WITH OR WITHOUT STRENGHENING ON PUNCHING SHEAR STRENGTH FOR REINFORCED CONCRETE FLAT PLATES - Abeer H.H. Al-Shammari (Journal of Engineering, 2011)
Reinforced concrete slabs with openings are usually designed with help of traditional rules proposed by building codes. Such methods introduce limitations concerning size, location of openings and magnitude of applied loads. Furthermore, there are some traditional approaches to strengthen reinforced concrete slabs with openings which can be either cumbersome or expensive. This paper studies variable locations of an opening with respect to a central column in reinforced concrete flat plates, and presents a good approach to strengthen this opening by using steel plates. Nine reinforced concrete flat plates are cast with dimensions (length, width and thickness) equal to (850, 470 and 50) mm) using a single concrete mix with average compressive strength (fcu) equals 30 MPa. Each slab contains a square cross-section opening (side length =75 mm) and supported by a central square crosssection column (side length =75 mm). The variables of this study are: the type of opening (with or without strengthening) and the clear distance between the opening and the column which takes the values (0.0d, 2d, 4.5d and 7d), where d is the effective depth. The specimens are tested over a simply supported span at four edges.The test results show that, the ultimate load reaches the maximum value for slab without opening while this load reaches the minimum value for slab with a non-strengthening opening and lies in the pattern of the failure zone (where the clear distance between the column and the opening equals 4.5d). When a comparison is made between the test results ,it is concluded that ;strengthening the slab opening with steel plates causes increasing in the ultimate load by (19.44 ,19.51 ,35.13 and 13.46) % for the specimens (0.0d ,2d ,4.5d and 7d ) respectively.